2014
DOI: 10.1002/2013jb010561
|View full text |Cite
|
Sign up to set email alerts
|

Seismic anisotropy and mantle flow beneath the northern Great Plains of North America

Abstract: A diverse set of tectonic features and the recent availability of high-quality broadband seismic data from the USArray and other stations on the northern Great Plains of North America provide a distinct opportunity to test different anisotropy-forming mechanisms. A total of 4138 pairs of well-defined splitting parameters observed at 445 stations show systematic spatial variations of anisotropic characteristics. Azimuthally invariant fast orientations subparallel to the absolute plate motion (APM) direction are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 70 publications
2
39
1
Order By: Relevance
“…The resulting depth estimates, when compared with the thickness of the lithosphere proposed by previous seismic tomographic studies [ van der Lee , ; Li et al , ; Yuan and Romanowicz , ], suggest that the observed anisotropy is mostly from the upper asthenosphere. This conclusion of mainly asthenospheric origin is consistent with that obtained in the central U.S. based on the same spatial coherency procedure [ Refayee et al , ; Yang et al , ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The resulting depth estimates, when compared with the thickness of the lithosphere proposed by previous seismic tomographic studies [ van der Lee , ; Li et al , ; Yuan and Romanowicz , ], suggest that the observed anisotropy is mostly from the upper asthenosphere. This conclusion of mainly asthenospheric origin is consistent with that obtained in the central U.S. based on the same spatial coherency procedure [ Refayee et al , ; Yang et al , ].…”
Section: Discussionsupporting
confidence: 90%
“…On the horizontal plane, the strike of the keel makes a sharp turn in the northern part of the study area and becomes mostly E‐W, as exemplified by one of the recent tomographic images (Figure ) [ Burdick et al , ]. The SWS observations can be well explained by a simple model involving both APM‐induced fabric and a mantle flow system deflected horizontally around the lateral edges of the keel of the North American Craton [ Fouch et al , ; Refayee et al , ; Yang et al , ]. We propose that the APM‐induced flow system ( V c ) is mainly developed in the transitional layer between the partially coupled lithosphere and the asthenosphere and is present beneath the entire area, while the horizontally deflected flow system exists only beneath the cratonic edges and goes around the keel (Figure ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Under the assumption that this zone represents the approximate edge of the African continental root, E‐W oriented asthenospheric flow locally deflected by the root can explain the E‐W fast orientations. Such a modulation of mantle flow by a continental root has been used to explain edge‐parallel fast orientations around the western and southern edges of the North American continental root [ Fouch et al ., ; Refayee et al ., ; Yang et al ., ]. It has also been suggested beneath central America [ Miller and Becker , ] and NW Africa [ Miller et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous geodynamic modeling and seismic anisotropy studies suggest that the rheologically different lithosphere and asthenosphere interact through partial coupling [ Becker and O'Connell , ; Marone and Romanowicz , ; Doglioni et al ., ; Refayee et al ., ; Yang et al ., ]. The direction of the simple shear in the boundary layer between the partially coupled lithosphere and asthenosphere is determined by the relative velocities between the two layers.…”
Section: Introductionmentioning
confidence: 99%